PARALINGUISTICS AS A TRANSLATOR OF LIVE COMMUNICATION (Scientific journal of the Fergana State University, 2024)
In todayʼs era of globalization, there is a growing body of research focused on new directions in linguistics that examine the language in close association with people. Paralinguistics, as a field that reflects the connection between language, society and humans. Paralinguistics offers a deeper understanding and insight into the study of human communication as an interpreter of live communication. Communication is not only limited to verbal tools, as non-verbal cues play a crucial role as well. This article explores the preservation and potential harm to oneʼs social image during the communication process, which is closely linked to the use of paralinguistic cues.